Molecular imprinting: perspectives and applications. (3rd March 2016) - Chen, Lingxin; Wang, Xiaoyan; Lu, Wenhui; Wu, Xiaqing; Li, Jinhua
Abstract : This critical review presents a survey of recent developments in technologies and strategies for the preparation of MIPs, followed by the application of MIPs in sample pretreatment, chromatographic separation and chemical sensing. Abstract : Molecular imprinting technology (MIT), often described as a method of making a molecular lock to match a molecular key, is a technique for the creation of molecularly imprinted polymers (MIPs) with tailor-made binding sites complementary to the template molecules in shape, size and functional groups. Owing to their unique features of structure predictability, recognition specificity and application universality, MIPs have found a wide range of applications in various fields. Herein, we propose to comprehensively review the recent advances in molecular imprinting including versatile perspectives and applications, concerning novel preparation technologies and strategies of MIT, and highlight the applications of MIPs. The fundamentals of MIPs involving essential elements, preparation procedures and characterization methods are briefly outlined. Smart MIT for MIPs is especially highlighted including ingenious MIT (surface imprinting, nanoimprinting, etc. ), special strategies of MIT (dummy imprinting, segment imprinting, etc. ) and stimuli-responsive MIT (single/dual/multi-responsive technology). By virtue of smart MIT, new formatted MIPs gain popularity for versatile applications, including sample pretreatment/chromatographic separation (solid phase extraction, monolithic column chromatography, etc. ) and chemical/biological sensing (electrochemical sensing, fluorescence sensing, etc. ). Finally, we propose the remaining challenges and future perspectives to accelerate the development of MIT, and to utilize it for further developing versatile MIPs with a wide range of applications (650 references).